2022
DOI: 10.1155/2022/9919839
|View full text |Cite|
|
Sign up to set email alerts
|

Acupuncture and Moxibustion in the Treatment of Adult Diarrhea Irritable Bowel Syndrome: A Network Meta-analysis

Abstract: Objective. This study was aimed at comparing the clinical efficacy of acupuncture and moxibustion on irritable bowel syndrome complicated with diarrhea (IBS-D) in adults and providing guidance for clinical treatment. Methods. PubMed, The Cochrane Library, Embase, CBM, CNKI, and VIP and Wanfang databases were searched to obtain clinical randomized controlled trials (RCTs) on acupuncture and moxibustion in the treatment of IBS-D published from establishment of the database to August 5, 2021. Relevant data were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In sham control trials, acupuncture did not yield strong, conclusive evidence, but moxibustion produced effects with substantial heterogeneity. More rigorous sham control trials, the authors warn, are needed to evaluate if acupuncture or moxibustion is beneficial in treating IBS [ 81 , 82 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In sham control trials, acupuncture did not yield strong, conclusive evidence, but moxibustion produced effects with substantial heterogeneity. More rigorous sham control trials, the authors warn, are needed to evaluate if acupuncture or moxibustion is beneficial in treating IBS [ 81 , 82 ].…”
Section: Reviewmentioning
confidence: 99%
“…Future research must have a stricter design and uniform reports. More research and meta-analyses are needed to assess how effective acupuncture is in treating IBS [ 82 ].…”
Section: Reviewmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%